Au-delà du plaisir visuel: féminisme, énigmes, cinéphilie - Mulvey, Laura (Formes filmiques, 2017)
En 1975, Laura Mulvey publie Plaisir visuel et cinéma narratif, texte polémique qui met en lumière la manière dont la forme filmique serait structurée par l’inconscient de la société patriarcale. C’est l’essai fondateur des études féministes sur le cinéma. Rédigés entre 1975 et 2011, les textes choisis dans ce volume sont marqués par la redécouverte féministe de la psychanalyse et les transformations induites par le développement des technologies numériques. Qu’elle s’attache à des genres ou à des auteurs incontournables (le western, le mélodrame, Ophüls, Hitchcock, Godard), qu’elle incarne l’avènement d’un « spectateur pensif », qu’elle analyse les paradoxes de l’esthétique hollywoodienne ou la compilation de films de propagande coloniale, Laura Mulvey fait preuve d’une cinéphilie active et engagée.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; cinema hollywoodien; cinéma; com5170; communication; corps; cours; discipline; discours dominant; europe; har4600; histoire de l'art; histoire et politique; male gaze; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; regard masculin; royaume-uni; régions géographiques; sofia; systèmes d'oppressions; thématiques; théorie du cinéma; états-unis

Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Impact féministe sur l'art actuel: La Centrale à 40 ans = Feminist impact on contemporary art : La Centrale at 40 - Burisch, Nicole (La Centrale Galerie Powerhouse, 2015)
"Publication, célébrant les 40 ans d'engagement de la Centrale qui se voue au développement de l'histoire des pratiques artistiques féministes et soutient la visibilité d'artistes et d'initiatives moins ou peu représenté-es auprès des institutions culturelles établies"--Page 40.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; périodes historiques; québec; régions géographiques; sex1911; thématiques

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, attitudes performatives, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France); Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Collection Nouvelles scènes, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

La traversée de la pornographie : politique et érotisme dans l'art féministe - Lavigne, Julie (Les éditions du remue-ménage, 2014)
On associe d’ordinaire l’érotisme aux femmes et la pornographie aux hommes. Puis, il y a des œuvres comme Romance de Breillat ou Baise-moi de Despentes et Trinh Thi pour tout ébranler, pour faire voler en éclats ce postulat désuet. Depuis plus de vingt ans, une forme de «métapornographie» veut proposer une représentation de la sexualité des femmes sans l’objectiver ni l’essentialiser, loin du paternalisme et de la victimisation. Des artistes filment leurs propres relations sexuelles, réutilisent des images de l’industrie de la porno ou offrent des performances explicites, tout en se revendiquant féministes. Mais la question de la pornographie, tant en histoire de l’art que dans les études féministes, est un terrain miné. Julie Lavigne se demande d’entrée de jeu comment cette dernière peut devenir meurtrière pour les unes et libératrice pour les autres. Les artistes qui s’approprient les codes de la porno commerciale pour les travestir ne jouent-elles pas au fond le jeu du conformisme? Selon quels critères une œuvre pornographique devient-elle artistique? L’excitation sexuelle est-elle compatible avec un discours critique? Cet essai audacieux explore le phénomène de la pornographie féministe en arts visuels, entre politique et intersubjectivité, en s’appuyant sur les théories de Georges Bataille et de Linda Williams, notamment. Il revisite les œuvres des pionnières Carolee Schneemann, Pipilotti Rist, Annie Sprinkle et Marlene Dumas. «L’analyse que La traversée de la pornographie propose se veut une valorisation d’un travail visuel controversé mais indispensable au regard critique et à la compréhension des féminismes, dont la pluralité demeure saine.» Thérèse St-Gelais, extrait de la préface
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; corps; cours; discipline; fem1000; har4600; histoire de l'art; pornographie; premier cycle; périodes historiques; sexualité; thématiques; érotisme

La rébellion du deuxième sexe : l'histoire de l'art au crible des théories féministes anglo-américaines (1970-2000) - Dumont, Fabienne (Les presses du réel, 2011)
Cette anthologie, la première du genre en langue française, retrace l'histoire complexe de quarante années de théories féministes anglo-américaines en histoire de l'art, à partir d'exemples détaillés et emblématiques. Les premiers écrits abordent l'histoire des pionnières de cette théorisation féministe, avec des écrits de Lucy Lippard, une analyse rétrospective des caractéristiques du mouvement californien des années 1970 ou des réceptions polémiques de The Dinner Party. Une seconde partie est consacrée à des textes qui s'attachent à une relecture de l'histoire de l'art des siècles passés, que ce soit le point de vue de Griselda Pollock, des « vieilles maîtresses » à une théorisation des espaces de la féminité, ou des approches plus marxistes du travail des artistes. Le troisième volet regroupe de nouvelles perspectives : l'analyse des masculinités à l'époque moderne et dans les performances des années 1960-1970, puis une approche des problématiques spécifiques aux artistes de couleurs, notamment afro-américaines. Enfin, deux études permettent de faire le point sur le développement postféministe en art et les questions queer. Cette sélection, issue d'un vaste répertoire, permet d'aborder les différentes conceptions théoriques des études féministes, de genre et queer en art qui se sont succédées et répondues des années 1970 aux années 2000.
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; amériques; anthologie; approches et analyses; cours; discipline; europe; fem1000; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; thématiques; états-unis

Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

Art et féminisme - Reckitt, Helena; Phelan, Peggy; Reckitt, Helena; Phelan, Peggy (Phaidon, 2011)
Depuis la fin des années 1960, le mouvement féministe a été à l'origine d'innovations, à la fois théoriques et pratiques, qui figurent parmi les plus intéressantes de l'art contemporain. Par ailleurs, certains succès politiques du mouvement féministe ont été obtenus grâce aux artistes, qui ont proposé de nouvelles manières d'envisager les domaines privé et public, l'objet de l'art et son sujet. En soulignant la différence des sexes, le courant féministe a aussi attiré l'attention sur le rôle de l'âge, de la classe sociale, de la race et de la sexualité dans la création artistique et dans sa réception. À la fois critiques et actrices du monde de l'art, les artistes féministes ont donné un nouvel élan à l'art considéré comme démarche à la fois politique et esthétique. Cet ouvrage, conçu par Helena Reckitt, présente les expériences, les idées et les démarches actuelles d'artistes majeures, et met en évidence le lien existant entre les différentes générations d'artistes. L'essai de Peggy Phelan, théoricienne de l'art et de la performance, jette un regard original sur les interprétations classiques de l'art des femmes et propose de nouvelles clés pour comprendre les rapports mouvants entre idées et idéaux du féminisme et pratiques artistiques.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques; théorie de l'art

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Caught in the act: an anthology of performance art by Canadian women - Mars, Tanya; Householder, Johanna; Mars, Tanya; Householder, Johanna (YYZ Books, 2004)
This indispensable anthology gives readers access to an important and under-recognized subject in recent Canadian art history. Edited by two seminal Canadian performance artists, this book focuses on the 70s and 80s; a time when women made a big and noisy impact. Full of sass and insight, this essential collection is part survey, part critical discourse, and part reference book, containing five critical essays, thirty-four artist's profiles, and an extensive bibliography.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; art contemporain; arts; canada; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques

Corps, sexe et art: dimension symbolique - Pearl, Lydie (Nouvelles études anthropologiques, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques

Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Performing the body: performing the text - Jones, Amelia..; Stephenson, Andrew; Jones, Amelia; Stephenson, Andrew (Routledge, 1999)
This book explores the new performativity in art theory and practice, examining ways of rethinking interpretive processes in visual culture. Since the 1960s, visual art practices - from body art to minimalism - have taken contemporary art outside the museum and gallery; by embracing theatricality and performance and exploding the boundaries set by traditional art criticism. The contributors argue that interpretation needs to be recognised as much more dynamic and contingent. Offering its own performance script, and embracing both canonical fine artists such as Manet, De Kooning and Jasper Johns, and performance artists such as Vito Acconci and Gunter Brus, this book offers radical re-readings of art works and points confidently towards new models for understanding art.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; premier cycle; périodes historiques; thématiques

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

Féminisme, art et histoire de l'art - Tucker, Marcia; École nationale supérieure des beaux-arts (France) (Espaces de l'art, 1994)
Ces cinq contributions d'historiennes de l'art et de femmes agissant dans le monde de l'art posent la question des apports du féminisme à l'art récent et au renouvellement de l'histoire de l'art, discipline largement régie, jusqu'au début des années 70, par le regard des hommes. Le féminisme a contribué à renouveler notre conception de l'art. Les auteurs de ce recueil comptent parmi les figures majeures de ce débat.
Keywords: 1900-1999; 1970-1979; 1980-1989; art occidental; arts; cours; discipline; har4600; har4610; histoire de l'art; premier cycle; périodes historiques

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Popular culture critical readers, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. --back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"--
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis

From the center: feminist essays on women's art - Lippard, Lucy R. (Dutton paperback original, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis